Comparison of endoscopic ultrasound-guided fine-needle aspiration and fine-needle biopsy to generate pancreatic cancer organoids: Randomized trial - Wiessner, Johannes Roman; Orben, Felix; Schäfer, Arlett; Fricke, Lisa; Schneider, Günter; Reichert, Maximilian; Herner, Alexander; Mayr, Ulrich; Phillip, Veit; Treiber, Matthias; von Figura, Guido; Abdelhafez, Mohamed; Schmid, Roland M.; Schlag, Christoph (Endoscopy International Open, 2024)
Background and study aims The prognosis for pancreatic cancer remains poor. Molecular diagnostics and customized therapies are becoming increasingly important in clinical routine. Patient-derived, predictive model systems such as organoids have the potential to substantially increase the depth of information from biopsy material by functional and molecular characterization. We compared the extent to which the use of fine-needle aspiration needles (FNA, 22G) or fine-needle biopsy needles (FNB, 22G) influences the generation of pancreatic cancer patient-derived organoids (PDOs) to establish endoscopic standards of organoid technology.Patients and methods Endoscopic ultrasound (EUS)-guided punctures by EUS-FNA and EUS-FNB of pancreatic masses highly suspicious for adenocarcinoma (detected by computed tomography and/or magnetic resonance imaging) were prospectively evaluated. Consecutive patients received EUS-FNA and EUS-FNB in a randomized order without the need to exchange the needle shaft (only the inner needle type (FNA/-B) was exchanged) between the passes. With each needle type, the specimens for histological analysis and for PDOs were obtained separately.Results Fifty patients were enrolled in the study. Histology revealed malignancy in 42 of 50 cases (84%). In total PDOs were generated from 17 patients (34%). Of these, nine were established by FNB only, two by FNA only, and six by both FNA and FNB. Histology revealed malignancy in 13 of 17 PDO cases (76%). In two histologically false-negative cases, PDOs could be established.Conclusions EUS-FNB was superior to EUS-FNA in terms of successful generation of PDOs, although it failed to show statistical significance.
Keywords: Endoscopic ultrasonography; Pancreas; Tissue diagnosis; Fine-needle aspiration/biopsy